2013
DOI: 10.1001/jama.2013.1363
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Fibrosis With Mortality and Sudden Cardiac Death in Patients With Nonischemic Dilated Cardiomyopathy

Abstract: ONISCHEMIC DILATED CARDIomyopathy is a common heart muscle disease with a prevalence of at least 1 in 2500 adults. 1 It is characterized by left ventricular cavity enlargement and impaired contractility in the absence of significant coronary artery disease. 1 The condition is associated with significant morbidity and mortality due to progressive heart failure (HF) and sudden cardiac death (SCD). 2 Despite For editorial comment see p 929.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
734
8
17

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 971 publications
(816 citation statements)
references
References 51 publications
29
734
8
17
Order By: Relevance
“…The overall favorable prognosis of PPCM where most women recover systolic function and fare well2 suggests a low prevalence of LGE. Yet, a recent study by Haghikia and colleagues reported an unexpectedly high prevalence of LGE (71%)3 in PPCM, which greatly exceeds the ≈30% prevalence of LGE reported in large case series of dilated cardiomyopathy patients 4. The reported high prevalence of LGE in PPCM appears at odds with the clinical course of PPCM as well as prior reports from smaller PPCM case series 5, 6, 7.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…The overall favorable prognosis of PPCM where most women recover systolic function and fare well2 suggests a low prevalence of LGE. Yet, a recent study by Haghikia and colleagues reported an unexpectedly high prevalence of LGE (71%)3 in PPCM, which greatly exceeds the ≈30% prevalence of LGE reported in large case series of dilated cardiomyopathy patients 4. The reported high prevalence of LGE in PPCM appears at odds with the clinical course of PPCM as well as prior reports from smaller PPCM case series 5, 6, 7.…”
Section: Introductionmentioning
confidence: 77%
“…CMR has emerged as an important tool to identify the etiology of nonischemic cardiomyopathies,27 and predict risk of adverse outcomes based on the extent of LGE 4, 8, 10, 14, 15, 27. LGE can detect foci of myocardial damage as small as 0.7 g of myocardial tissue 28.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations